New 3D supramolecular Zn(ii)-coordinated self-assembled organic networks - Lim, Zheng Bang (2013)
New 3D supramolecular networks S1 and S2 were prepared by Zn(II) coordination of the tetraphenylmethane-based p-type and n-type molecules bearing four terpyridine ligands. XRD and BET results indicate they are relatively amorphous and non-porous with a high degree of interpenetration within the networks. These could be disassembled by adding more Zn(II) ions and re-assembled to form extended 3D networks S3–6 by inserting linear n-type or p-type linking units. BET data suggests that these expanded networks are more porous than the original networks S1–2, but the low porosity and surface area suggest a high degree of interpenetration remains within the expanded networks. The optical properties of these materials were compared to the linear polymers P1–3 made by Zn(II)-mediated assembly of the same linear linking units. The emission spectra of both the 3-D and 1-D cases with the same linking unit matched each other, confirming the incorporation of the linker units into the expanded assemblies. This shows that metal–ligand mediated self-assembly can be used to make two component systems in which the optical properties can be tuned by selection of the units. The assembly was also performed in the presence of CdSe nanocrystals to form nanocomposites.